2019
DOI: 10.1021/acs.cgd.9b01541
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydrogen Bonding in Phase Change Materials

Abstract: Phase change materials (PCMs) which melt in the temperature range of 100-230 °C, are a promising alternative for the storage of thermal energy. In this range, large amounts of energy available from solar-thermal, or other forms of renewable heat, can be stored and applied to domestic or industrial processes, or to an Organic Rankine Cycle (ORC) engine to generate electricity. The amount of energy absorbed is related to the latent heat of fusion (ΔH f) and is often connected to the extent of hydrogen bonding in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 44 publications
1
47
0
Order By: Relevance
“…There exists intermolecular hydrogen bonding O–H⋯O formed by the carboxylic group as the donor and carbonyl group as the accepter. It is worth mentioning that hydrogen bonding is beneficial to the stabilization of ordered molecules in the LTP and thus greatly contributes to the high T c of the crystal 47,48 and further reservation of its ferroelectricity at a higher temperature. 49 …”
Section: Resultsmentioning
confidence: 99%
“…There exists intermolecular hydrogen bonding O–H⋯O formed by the carboxylic group as the donor and carbonyl group as the accepter. It is worth mentioning that hydrogen bonding is beneficial to the stabilization of ordered molecules in the LTP and thus greatly contributes to the high T c of the crystal 47,48 and further reservation of its ferroelectricity at a higher temperature. 49 …”
Section: Resultsmentioning
confidence: 99%
“…That is, a larger number of intermolecular hydrogen bonds in the solid phase causes a stable solid phase in terms of electrostatic energy. In addition, Matuszek et al [35] found that latent heat depends on the concentration and strength of hydrogen bonding present in the crystal structure and on the extent of disruption of the crystal phase at elevated temperatures. The same author mentioned that an ideal PCM is one in which many strong hydrogen bonds are present in the crystalline phase and which are readily disrupted on melting.…”
Section: Latent Heat Degradationmentioning
confidence: 99%
“…Thermal energy storage materials are needed across a broad temperature range to, for instance, reduce the energy required to heat and cool buildings (25–150 °C), , optimize the efficiency of thermoelectrics (25–650 °C), , dissipate heat in electronics and data centers (30–80 °C), , increase the driving range of electric vehicles in cold climates (30–60 °C), recover waste heat from industrial processes (40–1000 °C), reduce emissions from combustion vehicle cold starts (250–350 °C), , and store solar energy (250–1000 °C) . Despite the tremendous importance of managing heat efficiently, the development of new thermal energy storage materials has received significantly less attention than materials for electrical and chemical energy storage, particularly within the synthetic chemistry community. …”
Section: Introductionmentioning
confidence: 99%
“…The development of PCMs has continued to focus on simple inorganic and organic compounds, frequently relying on external systems or internal additives to augment the properties of existing materials. These efforts have led to the commercialization of a range of PCMs, but their energy density and overall performance have not been sufficient to warrant their use in many thermal applications. Given that engineering solutions increase the mass, volume, cost, and complexity of thermal energy storage systems, there has been surprisingly little effort to synthesize and evaluate new PCMs that might offer intrinsically better properties. , In particular, although metal–salt hydrates have received substantial attention, structurally similar metal–organic materials have yet to be seriously explored in the context of thermal energy storage despite their diverse range of modular and highly tunable structures. Unlike conventional organic and inorganic PCMs, the structure of metal–organic materials can be controlled through rational ligand design and directional coordination bonds to tailor the dimensionality, entropy, and strength of covalent and noncovalent interactions within a solid in a predictable fashion. , Beyond the potential implications for improved performance, tunable metal–organic PCMs offer a platform to establish fundamental structure–property relationships that provide insight into the thermodynamics and kinetics of phase transitions relevant to thermal energy storage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation